The Implementation of Kagan’s Cooperative (Co-Op) Technique to Improve Reading Comprehension of Junior High Students - Farid Helmi Setyawan (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2017)
Abstract: This study was aimed to investigate how Co-op technique can be implemented to improve reading comprehension of the eighth grade students of MTsN Ngawi who faced the problems in reading. The students did not comprehend the text and the score was low. The average score of reading test in preliminary study was 67 where as the average score of student’ success based on the minimum standard of students’ score is seventy (70). The design of this study was classroom action research. The technique applied in the research was Co-op technique. The result showed that the students reading average score significantly improved. In two cycle study, in the first test the students reading average score was 69.54, in the second test the students reading score was 76.15. It could be concluded that predetermined criteria of success had been achieved.